2016
DOI: 10.1056/nejmoa1502924
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trials of rVSV Ebola Vaccine in Africa and Europe

Abstract: BACKGROUNDThe replication-competent recombinant vesicular stomatitis virus (rVSV)-based vaccine expressing a Zaire ebolavirus (ZEBOV) glycoprotein was selected for rapid safety and immunogenicity testing before its use in West Africa. METHODSWe performed three open-label, dose-escalation phase 1 trials and one randomized, double-blind, controlled phase 1 trial to assess the safety, side-effect profile, and immunogenicity of rVSV-ZEBOV at various doses in 158 healthy adults in Europe and Africa. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
458
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 379 publications
(489 citation statements)
references
References 30 publications
20
458
3
8
Order By: Relevance
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…6,7 These studies showed that the vaccine was immunogenic, with higher titres of neutralising antibodies produced at higher vaccine doses, 7 but the glycoprotein antibody titres were measured only at baseline and at 28 days post-vaccination. Although no data are yet available for the time needed for the vaccine to induce protective immunity, our results suggest that this might happen quickly, within a few days or a week.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, at present, no licensed vaccines are available, despite promising results for several candidate vaccines in non-human primate studies and phase 1 trials. [2][3][4][5][6][7][8][9] The recombinant, replication-competent vesicular stomatitis virus-based candidate vaccine expressing the glycoprotein of a Zaire Ebolavirus (rVSV-ZEBOV) causes a transient systemic infection after a single injection, and produces a rapid immune response against the Ebola virus surface protein. 6,7 The Ebola ça Suffi t ("Ebola this is enough") clusterrandomised phase 3 trial is currently underway in Guinea to assess the effi cacy of the rVSV-ZEBOV candidate vaccine for the prevention of Ebola virus disease.…”
Section: Introductionmentioning
confidence: 99%
“…12,14,[48][49][50][51][52] The first 3 open-label, uncontrolled, phase I clinical trials of rVSV-EBOV vaccine were conducted in Lambar en e, Kilifi, and Hamburg, respectively, which were designed to assess the safety, and immunogenicity of escalating doses ranging from 3 £ 10 5 to 2 £ 10 7 vp in early 2014 (NCT02283099, NCT02287480, NCT02296983) ( Table 1). 53 The preliminary results of the rVSV-EBOV vaccine from the above 3 trials, involving a total of 99 participants, demonstrated a good immunogenicity, but a mild to moderate reactions related to vaccination (Table 4).…”
Section: Rvsv-ebovmentioning
confidence: 96%